The challenges to the design and implementation of youth and adolescent health policy in Sekhukhune District - Limpopo Province - Mathunyane, Mampe Martha (University of Limpopo (Turfloop Campus), 2012)
The research was undertaken to determine the challenges in the design and implementation of the youth and adolescent health policy. Special attention was focused on the design of the policy and people involved in policy development and implementation. Literature indicates that development and implementation of youth and adolescent health policy is a multisectoral, complex dynamic process. The study was undertaken to establish to what extent was the multisectoral approach implemented in Sekhukhune district, Limpopo province. The aim of the study was twofold: To study the problem of implementation of the youth and adolescent health policy and recommend ways of improving implementation; and to establish the appropriate model of implementation of the youth and adolescent health policy. The objectives of the study, were to determine the role of delegated officials regarding the implementation of the youth and adolescent health policy in Sekhukhune district. To establish if the delegated officials had the knowledge and skills to implement the youth and adolescent health policy as laid out by the National Department of Health, and to establish the extent to which interest groups such as School Governing Bodies, Non-Governmental organisations and traditional leaders were involved and participated in implementing the youth and adolescent health policy. The significance of the study was to assist in assessing the extent to which the youth and adolescent health policy was implemented in Sekhukhune district in Limpopo province. The research methodology was qualitative interviews. The Department of Health, district office, health institutions (health centres and clinics, and hospitals) were visited by the researcher. Structured interviews were conducted on the selected sample of health workers and youth. The sample size was 50: 40 were health workers and 10 youths in the area where the research was conducted, represented the youth. One office in the Department of health, Limpopo province, Sekhukhune district office, 3 hospitals, 5 municipal offices (health offices) 15 primary health care facilities(clinics) were visited and one to one interview, using a questionnaire, was conducted in order to ensure confidentiality. The findings were that there were health workers who were not aware of the availability of the youth and adolescent health policy. The Department of health did not have guidelines/policies on how to implement National health policies. Health workers at health institutions (hospitals) were interested in knowing more about the youth and adolescent health policy. The youth made suggestions for the improvement of recreation facilities and that health services for the youth should be more accessible, by separating the youth from adults at primary health care facilities. Most health workers expressed the need for training on the implementation of the youth and adolescent health policy.
Thesis (MPA) --University of Limpopo, 2010
Keywords: Youth; Adolescents health policy; 305.2350968; Adolescence; Youth -- Service for -- South Africa